PELAKSANAAN HUKUMAN TERPIDANA KORUPSI DI LEMBAGA PEMASYARAKATAN KELAS IIA SAMARINDA - Gusti Lili Eriyanti (Universitas 17 Agustus 1945 Samarinda, 2019)
Abstract Correctionalism is essentially an idea in carrying out imprisonment while upholding the dignity and dignity of a human being. The treatment was intended to return prisoners to the community as good and useful people. To undergo the implementation system, community participation or participation is needed, either by organizing cooperation in coaching or by being willing to accept returning prisoners who have finished serving their crimes. The implementation and guidance that is applied in Correctional Institutions for corruption convicts is a person who has knowledge that is very high and has integrity. Therefore, this study aims to find out the implementation of knowing the execution of penalties for convicted corruption and to find out the guidance of corruption convicts in Correctional Institutions. The research method used in this study is a juridical-normative approach method, namely research conducted directly to the location of the study. With the research location at the Class IIA Penitentiary of Kota Samarinda on Jalan Jend. Sudirman No.15, Kota Samarinda, East Kalimantan. The types and sources of data used are primary data and secondary data. Based on the results of the research Likewise the execution of the convicts of corruption convicts was placed in detention in a prison institution, for guidance and punishment. The implementation of the sentence while in detention Correctional Institution runs all activities based on Pancasila in order to improve the quality of corruption convicts as prisoners to realize and not repeat mistakes, improve themselves not to repeat crimes so that they can be accepted again by the community, can actively play a role in development and can live naturally as a good and responsible citizen, while the implementation of guidance carried out on convicted corruption in practice, Until now Correctional Institutions do not have specific guidance guidelines for convicted corruption, so it still refers to guidance carried out on convicts, including general crimes . But in reality Correctional Institutions have problems because of differences. The difference here is not the difference in treatment, but the differences in characteristics between the convicted corruption and other convicts, both their economic level, education, and integrity. Keywords: Penitentiary, Implementation, Coaching, corruption